Saving Indonesia's Golden Generation: Preventing Teenage Marriage in Rembang, Central Java (A Case Study) - Partini Partini; Hermin Indah Wahyuni; Lidwina Mutia Sadasri (Center for Southeast Asian Social Studies (CESASS), 2020)
Indonesia is expected to reap the benefits of a golden generation, enjoying an advanced and independent modern society in the year of 2045. However, there are great challenges ahead including problems amongst younger Indonesians which may hinder the realization of this projection. This study brings to the fore the problem of teenage marriage, defined as the marriage of two individuals under the age of eighteen, be it through coercion or through their own volition. Data show that 14.18% of married Indonesian women are younger than 16 years old (SUSENAS, 2017); with 1.459,000 teenage girls marrying per annum so that the country ranks eighth globally in terms of teenage marriage (UNICEF, 2020). Using a cybernetics communication approach and qualitative method, this article assesses teenage marriage prevention programs in Rembang, a regency in middle Java, Indonesia. This study found that prevention of teenage marriage is not part of everyday discussion in the grassroots. Public discourse has stalled at the information stage, optimal understanding has yet to be realized. With this backdrop, Rembang regency utilize a top-down approach in organizing its teenage marriage prevention programs. However, synergy and cooperation remain necessary to minimize the practice by maximizing collaboration with families, schools, health officials, religious officials, and civil servants who turn to be the most influential actors in such programs.